Evolution of land distribution in West Bengal 1967-2004: Role of land reform - Pranab Bardhana; Michael Lucab; Dilip Mookherjeeb; Francisco Pinob (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
This paper uses data from a household survey to estimate changes in land distribution in rural West Bengal between 1967-2004 and decompose these into contributions of different factors. There was a substantial drop in land per household and land per capita, while within-village inequality rose. The latter was associated mainly with rising landlessness induced by high rates of household division for marginal and small landowning households. Conversely, division of large landowning households reduced inequality. We find a significant indirect effect of the tenancy reform (Operation Barga) on inequality, as it reduced division rates of small landowning households while raising those of large landowning households. The land titling (patta) program also reduced inequality by reducing landlessness. Land markets were highly active, and were mildly equalizing. The inequality reducing effects of land reforms and land markets were dwarfed by the rising inequality and landlessness induced by division of small landowning households and immigration.
Keywords: O13; O29; Q15; 330; household division; land inequality; land markets; land reform